1963
DOI: 10.1002/jsfa.2740141211
|View full text |Cite
|
Sign up to set email alerts
|

Non‐enzymic browning: The role of unsaturated carbonyl compounds as intermediates and of so2 as an inhibitor of browning

Abstract: The browning potentialities of a number of carbonyl compounds has been examined. From the results it is clear that most rapid browning with a reactive nitrogen function occurs with straight chain NP-unsaturated aldehydes. When the conjugated unsaturation is within a ring structure, as in the furfurals, chromophore development is slower. When the unsaturated centre is substitated, the browning rate is much reduced. Saturated carbonyl compounds are of relatively low browning potential.The retardation in the brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1964
1964
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…They also suggest that Maillard type reactions may be involved in mutagen formation and browning reaction inhibitors might diminish the levels of mutagens. As seen in Table 8, the introduction of NaBH4 or NaHSO3, both of which interact with carbonyl groups to block browning reactions (44,45), eliminated mutagen formation in the model systems, thus supporting the above conjecture.…”
Section: Model System Studiessupporting
confidence: 61%
“…They also suggest that Maillard type reactions may be involved in mutagen formation and browning reaction inhibitors might diminish the levels of mutagens. As seen in Table 8, the introduction of NaBH4 or NaHSO3, both of which interact with carbonyl groups to block browning reactions (44,45), eliminated mutagen formation in the model systems, thus supporting the above conjecture.…”
Section: Model System Studiessupporting
confidence: 61%
“…The amount of ascorbic acid in this study decreased by 50% during storage time as reported in other studies. The formation of browning depends on the degradation of ascorbic acid leading to the formation of carbonyl compounds [21][22][23].…”
Section: Effect Of Storage Time and Temperature On Orange Wine Colourmentioning
confidence: 99%
“…This observation suggested that DAA ) VIC reaction occurred in meat by heat treatment at higher temperature but the rate of its reaction was very slow. Burton et al 5 ) showed that a,,B-unsaturated straight chain aldehydes greatly accelerated by initial development of chromophores in foods, but this effect was not shown by the unsaturated aldehydes with alkyl substituent on the a-carbon atom (2,3-dialkyl acroleins). On the basis of these data, DAA seemed to be stable in meat.…”
Section: ) Change Of Daa Concentrationmentioning
confidence: 99%